An Empirical Study of Factors that Influence HRD Climate in Public Sector Industries - Savitha, K.M.; Martin Jayaraj, A. (International Journal of Psychosocial Rehabilitation, 2019)
Human Resource Development (HRD) has the origin of human resource management, which includes the training of employees. Human resource development involves training the employees and making them learn new skills, which are beneficial for their development. For any kind of organisation human resource is essential. It has various capabilities and potential, when compared to other resources. Human resource potential can be effectively utilized, only when the organisation climate is conducive to the development of employees. This made the researcher conduct “An Empirical study of factors that influence the climate of Human Resource Development in Public sector industries”. The researcher has framed the conceptual framework which includes factors like Manager Support, Openness, Team spirit and working environment. The researcher also distributed HRD climate questionnaire among the respondents and inferred that the HRD climate is moderate.